The War on Drugs and Crimes (International Journal of Innovative Research in Computer Science & Technology, 2022)
Drugs use and crimes have an intimate  relationship. All the persons who use drugs are not  criminals and all the criminals were not addicted to drugs.  But addiction to drugs is directly related to the increase in  normal and heinous crimes because of modified criminal  behavior. Apart from crimes, drugs play a very effective  role in communal, social, financial, and health  disturbances and damages. Most of the countries have been  facing problems with drugs use and crimes and are not free  from drug trafficking and manufacturing. Many researchers and policymakers believe except only drug use  leads to crime yet not crime lead to drug use. Drug abuse,  as well as Narcotics, had led to a harmful impact on  society. The types of drugs, ways of crimes, and their laws  play important role in the administration for a better  society.
Keywords: Narcotics; Drugs- Crimes; Criminal Behavior; Drug Trafficking; Drug Manufacturing